Pathogen exposure leads to a transcriptional downregulation of core cellular functions that may dampen the immune response in a macroalga. Issue 12 (4th May 2022) - Hudson, Jennifer; Deshpande, Nandan; Leblanc, Catherine; Egan, Suhelen
Abstract: Diseases in marine eukaryotic organisms caused by opportunistic pathogens represent a serious threat to our oceans with potential downstream consequences for ecosystem functioning. Disease outbreaks affecting macroalgae are of particular concern due to their critical role as habitat‐forming organisms. However, there is limited understanding of the molecular strategies used by macroalgae to respond to opportunistic pathogens. In this study, we used mRNA‐sequencing analysis to investigate the early antipathogen response of the model macroalga Delisea pulchra (Rhodophyta) under the environmental conditions that are known to promote the onset of disease. Using de novo assembly methods, 27, 586 unique transcripts belonging to D . pulchra were identified that were mostly affiliated with stress response and signal transduction processes. Differential gene expression analysis between a treatment with the known opportunistic pathogen, Aquimarina sp. AD1 (Bacteroidota), and a closely related benign strain ( Aquimarina sp. AD10) revealed a downregulation of genes coding for predicted protein metabolism, stress response, energy generation and photosynthesis functions. The rapid repression of genes coding for core cellular processes is likely to interfere with the macroalgal antipathogen response, later leading to infection, tissue damage and bleaching symptoms. Overall, this study provides valuable insight into the genetic features of D . pulchra, highlighting potential antipathogen response mechanisms of macroalgae and contributing to an improved understanding of host–pathogen interactions in a changing environment.